Effects of High Frequency Chest Compression on Respiratory System Mechanics in Normal Subjects and Cystic Fibrosis Patients - Richard L Jones; Richard T Lester; Neil E Brown (Canadian Respiratory Journal)
OBJECTIVE: To investigate the short term effects of high frequency chest compression (HFCC) on several indices of respiratory system mechanics in normal subjects and patients with cystic fibrosis (CF).